2022
DOI: 10.1186/s40001-022-00840-7
|View full text |Cite
|
Sign up to set email alerts
|

The underlying molecular mechanisms and biomarkers of plaque vulnerability based on bioinformatics analysis

Abstract: Aim The study aimed to identify the underlying differentially expressed genes (DEGs) and mechanism of unstable atherosclerotic plaque using bioinformatics methods. Methods GSE120521, which includes four unstable samples and four stable atherosclerotic samples, was downloaded from the GEO database. DEGs were identified using LIMMA. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of DEGs were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Together with PPARγ, CEBPA regulates the adipogenesis process and is involved in the sequence expression of adipocytespecific proteins [30][31][32][33][34][35][36]. CEBPA is upregulated in unstable plaques, and overexpression of CEBPA may contribute to the occurrence and development of atherosclerosis [37,38]. However, Bristol et al [39] observed that CEBPA and CEBPB bind the TNFR1 promoter, increase its expression through a positive feedback mechanism, and induce an increase in TNF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Together with PPARγ, CEBPA regulates the adipogenesis process and is involved in the sequence expression of adipocytespecific proteins [30][31][32][33][34][35][36]. CEBPA is upregulated in unstable plaques, and overexpression of CEBPA may contribute to the occurrence and development of atherosclerosis [37,38]. However, Bristol et al [39] observed that CEBPA and CEBPB bind the TNFR1 promoter, increase its expression through a positive feedback mechanism, and induce an increase in TNF expression.…”
Section: Discussionmentioning
confidence: 99%